IMAGE OF SPRING IN THE POETRY OF KUTLIBEKA RAHIMBOYEVA - Bozorova E'zoza Bakhriddin kizi (Scholar Express Journal, 2023)
This article analyzes the poem “One Spring Day” by poetess Qutlibeka Rahimboyeva. The poem contains comments on the importance of natural scenery, artistic and descriptive means, and symbolic expression of the inner experiences of the lyrical “I”. In the landscape lyrics, it is shown that the important aspects of life are manifested through nature.
Keywords: Landscape; the spirit of the author; lyrical; symbol